Reviews (Modern theology, 1999)
Ellen T. Charry, By the Renewing of Your Minds Francis Watson, Text and Truth: Redefining Biblical Theology Miroslav Volf, Exclusion and Embrace: A Theological Exploration of Identity, Otherness, and Reconciliation Catherine Pickstock, After Writing: On the Liturgical Consummation of Philosophy Mary M. Solberg, Compelling Knowledge Fergus Kerr, Immortal Longings: Versions of Transcending Humanity Graham Ward, Theology and Contemporary Critical Theory Diana Fritz Cates, Choosing to Feel: Virtue, Friendship, and Compassion for Friends Regina M. Schwartz, The Curse of Cain: The Violent Legacy of Monotheism Stephen Prickett, Origins of Narrative: The Romantic Appropriation of the Bible